A process and application of first extracting lithium and then extracting nickel, cobalt and manganese

By improving the stability and extraction efficiency of lithium adsorbents and combining with the improvement of microbial extraction methods, the problems of low lithium ion extraction efficiency in lithium batteries and susceptible to the environment are solved, and efficient and stable lithium ion extraction and nickel-cobalt are achieved. Manganese recycling, suitable for the production of ternary positive electrode materials.

CN118835084BActive Publication Date: 2025-02-07GUANGDONG WIIMAR NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410882026.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-03
Publication Date
2025-02-07
Estimated Expiration
2044-07-03

AI Technical Summary

Technical Problem

Existing lithium adsorbents are prone to dissolution and loss when dealing with lithium batteries, resulting in collapse of the adsorbent structure; microbial extraction methods are susceptible to temperature, humidity and environment, resulting in low adsorption efficiency.

Method used

Aluminum-based adsorbent is mixed with a silicon source and citric acid is added to form a silicon dioxide layer to improve stability; iminodiacetic acid is used to react with chloromethylated polystyrene to form a cross-linking network structure to improve lithium ions Extraction activity; mix porous carbon adsorption complex bacterial species with 2-naphthalene sulfonic acid to improve the activity and recovery efficiency of microbial extractant.

Benefits of technology

Directed extraction of lithium ions in lithium batteries is achieved, the stability and extraction efficiency of adsorbents are improved, the impact of lithium elements on subsequent nickel-cobalt-manganese extraction is reduced, and the impurity content in the ternary positive electrode material is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a process and application of first extracting lithium and then extracting nickel, cobalt and manganese, which belongs to the technical field of waste lithium battery recycling, and comprises the following steps: mixing pretreated positive electrode powder and organic acid solution, stirring, adding composite ion exchange resin, filtering, obtaining solid A and water extract, and obtaining lithium carbonate by post-treatment of solid A; mixing the water extract with composite microbial extractant, filtering, obtaining solid B, and obtaining nickel, cobalt and manganese salt by desorption treatment of solid B. The modified aluminum-based adsorbent is embedded in the cross-linked network structure to form a macroporous adsorption resin, which gives the macroporous adsorption resin a directional adsorption function for lithium ions, thereby first separating lithium ions from waste lithium batteries; the composite strain is adsorbed into the interior of porous carbon, and the remaining cobalt ions, manganese ions and nickel ions in the positive electrode powder water extract can be adsorbed into the interior of the porous carbon, avoiding the influence of other impurities, and improving the extraction rate of nickel, cobalt and manganese.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste lithium battery recycling, and specifically to a process method and application of first extracting lithium and then extracting nickel, cobalt and manganese. Background Art

[0002] Nickel cobalt manganese oxide positive electrode material is the main product of ternary lithium-ion batteries. With the development of the lithium-ion battery industry, the environmental pollution and resource waste caused by discarded ternary lithium-ion batteries are becoming increasingly serious. A large number of waste ternary lithium battery materials are rich in valuable elements such as lithium, nickel, cobalt, and manganese. The potential resource volume is huge and the economic value of recycling is high. The recycling process of waste lithium-ion battery positive electrode materials mainly includes pyrometallurgy, hydrometallurgy, bioleaching and direct recovery. The development of recycling and regeneration technology for waste ternary lithium battery materials will help prevent and control waste battery pollution, alleviate the shortage of nickel, cobalt and lithium resources, and promote the healthy development of the lithium battery industry.

[0003] Lithium batteries contain metal elements such as cobalt and nickel. If they are not recycled, it will not only cause a huge waste of resources, but also cause ecological pollution, thus limiting the sustainable development of the new energy vehicle industry. Lithium batteries are treated with lithium adsorbents. Lithium adsorbents have excellent lithium ion adsorption performance and can achieve directional extraction of lithium ions in lithium batteries, but lithium adsorbents are easy to dissolve and lose, resulting in the collapse of the adsorbent structure; organic or inorganic acids are produced through the metabolic activities of microorganisms to extract metal ions from lithium batteries, which is pollution-free and environmentally friendly, but these microorganisms are easily affected by temperature, humidity and environment, resulting in low adsorption efficiency. Summary of the invention

[0004] The invention mixes an aluminum-based adsorbent with a silicon source, and then adds citric acid. The aluminum-based adsorbent exhibits high selectivity for lithium ions. A silicon dioxide layer is synthesized on the surface of the aluminum-based adsorbent, thereby improving the stability of the aluminum-based adsorbent and preventing it from being easily decomposed. In addition, the citric acid increases the contact area between the aluminum-based adsorbent and the metal ion solution, thereby increasing the adsorption rate for lithium ions. Iminodiacetic acid reacts with chloromethylated polystyrene, and then the modified aluminum-based adsorbent is added and stirred for reaction. Iminodiacetic acid is grafted onto the molecular chain of the chloromethylated polystyrene as a metal ion chelating resin matrix, which has a higher binding site and improves the adsorption rate for lithium ions. The extraction activity of the modified aluminum-based adsorbent is embedded in the cross-linked network structure to form a macroporous adsorption resin, which gives the macroporous adsorption resin a directional adsorption function for lithium ions, and then can first separate lithium ions from waste lithium batteries; the porous carbon adsorbs the composite bacteria, and then mixes it with 2-naphthalenesulfonic acid, and adsorbs the composite bacteria into the interior of the porous carbon to improve the activity of the composite bacteria, avoid the composite bacteria being easily affected by temperature, humidity and environment, resulting in low adsorption efficiency, and the sulfonic acid group of 2-naphthalenesulfonic acid can combine with metal elements in waste lithium batteries, thereby improving the recovery efficiency of the composite microbial extractant for valuable metal ions.

[0005] The technical problem to be solved by the present invention is as follows: lithium batteries are treated with lithium adsorbents, which exhibit excellent lithium ion adsorption performance and can achieve directional extraction of lithium ions in lithium batteries, but lithium adsorbents are easily dissolved and lost, resulting in collapse of the adsorbent structure; organic or inorganic acids are produced through the metabolic activities of microorganisms to extract metal ions from lithium batteries, which is pollution-free and environmentally friendly, but these microorganisms are easily affected by temperature, humidity and environment, resulting in low adsorption efficiency.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A process for extracting lithium first and then nickel, cobalt and manganese comprises the following steps:

[0008] S1. Place the waste lithium battery in a sodium chloride solution for discharge, disassemble it, place it in a grinder for coarse crushing, pyrolyze it, and sieve it to obtain a pre-treated positive electrode powder.

[0009] Among them, the binder, conductive agent and organic matter in the waste lithium battery material are removed by high-temperature pyrolysis, thereby reducing the cohesive force between the coating material particles, weakening the adsorption force between the coating and the current collector, and achieving the initial separation between the electrode material and the current collector, which is beneficial to the subsequent extraction process.

[0010] Furthermore, the ratio of waste lithium batteries to sodium chloride solution is (30-40) g: (80-100) mL.

[0011] S2. The pretreated positive electrode powder and the organic acid solution are mixed, stirred, a composite ion exchange resin is added, filtered, and solid A and a water extract are obtained. The solid A is post-treated to obtain lithium carbonate.

[0012] Furthermore, the ratio of the pretreated positive electrode powder, the organic acid solution, and the composite ion exchange resin is (15-20) g: (60-80) mL: (3-7) g.

[0013] S3. The water extract is mixed with the composite microbial extractant, filtered, and solid B is obtained. The solid B is desorbed to obtain nickel-cobalt-manganese salt.

[0014] Furthermore, the dosage ratio of the water extract to the composite microbial extractant is (50-70) mL: (5-7) g.

[0015] Furthermore, the concentration of the sodium chloride solution is 1-3 mol / L.

[0016] Further preferably, the concentration of the sodium chloride solution is 2.7 mol / L.

[0017] Furthermore, the pyrolysis temperature is 200-600°C; and the sieve mesh size is 200-400 mesh.

[0018] More preferably, the pyrolysis temperature is 450° C. and the sieve mesh size is 300 mesh.

[0019] Furthermore, the organic acid solution is composed of organic acid and deionized water in a ratio of (10-12) g:(50-60) mL.

[0020] Furthermore, the organic acid is selected from any one of malic acid, oxalic acid and ascorbic acid.

[0021] Furthermore, the post-treatment of solid A specifically includes the following steps: adding solid A to deionized water, shaking at a rate of 60 rpm for 1 hour, collecting the filtrate by filtration, adding a sodium carbonate aqueous solution with a concentration of 0.2 g / mL to the filtrate, stirring at 80°C for 3 hours, filtering, washing with deionized water 3 times, and drying in an oven at 60°C for 10 minutes.

[0022] Furthermore, the dosage ratio of solid A, deionized water, and sodium carbonate aqueous solution is (3.6-4) g: (50-70) mL: (8-12) mL.

[0023] Furthermore, the desorption treatment of solid B specifically includes the following steps: adding solid B to a 2 mol / L nitric acid aqueous solution, soaking for 20 minutes to desorb metal ions, filtering, collecting the filtrate, stirring the filtrate at 90° C. for 2 hours, and cooling to room temperature.

[0024] Furthermore, the dosage ratio of solid B and aqueous nitric acid solution is (4.2-4.5) g:(25-35) mL.

[0025] Furthermore, the composite ion exchange resin is prepared by reacting iminodiacetic acid with chloromethylated polystyrene, adding a modified aluminum-based adsorbent, and stirring the reaction; specifically, the composite ion exchange resin is prepared by the following steps:

[0026] Add chloromethylated polystyrene to N,N-dimethylformamide, stir evenly, add iminodiacetic acid and sodium hydroxide, stir and react at 80°C for 1 hour, add modified aluminum-based adsorbent, stir and react at 80°C for 30 minutes, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10 minutes to obtain a composite ion exchange resin.

[0027] Among them, in the organic solvent N,N-dimethylformamide, sodium hydroxide is used as a catalyst, and the chlorine atoms in the chloromethylated polystyrene can undergo a substitution reaction with the amino groups in the iminodiacetic acid, so that the iminodiacetic acid is grafted on the chloromethylated polystyrene molecular chain, which serves as a metal ion chelating resin matrix with a higher binding site, thereby improving the extraction activity of lithium ions.

[0028] Furthermore, the chloromethylated polystyrene grafted with iminodiacetic acid is combined with the hydroxyl groups on the surface of the modified aluminum-based adsorbent through chemical bonds, consuming the carboxyl groups of the iminodiacetic acid to form a cross-linked network structure, and the modified aluminum-based adsorbent is embedded in the cross-linked network structure to form a macroporous adsorption resin, which gives the macroporous adsorption resin a directional adsorption function for lithium ions, thereby being able to first separate lithium ions from waste lithium batteries.

[0029] Furthermore, the dosage ratio of chloromethylated polystyrene, N,N-dimethylformamide, iminodiacetic acid, sodium hydroxide, and modified aluminum-based adsorbent is (5-7) g: (90-110) mL: (2-3) g: (0.1-0.3) g: (2-3) g.

[0030] Furthermore, the modified aluminum-based adsorbent is prepared by mixing the aluminum-based adsorbent with a silicon source and then adding citric acid.

[0031] Furthermore, the silicon source is selected from any one of tetraethyl orthosilicate, dimethyldiethoxysilane, and diphenyldiethoxysilane.

[0032] Furthermore, the modified aluminum-based adsorbent is specifically prepared by the following steps:

[0033] The aluminum-based adsorbent was added to a mixture of ethanol and deionized water, stirred evenly, 20% ammonia water was added, stirred evenly, 4 mL of silicon source tetraethyl orthosilicate was added, stirred and reacted for 2 h, filtered, washed with ethanol 3 times, washed with deionized water 3 times, dried in an oven at 45 °C for 30 min, placed in deionized water, stirred, citric acid was added, stirred and reacted at 70 °C for 30 min, filtered, washed with deionized water 3 times, and dried in an oven at 70 °C for 30 min to obtain a modified aluminum-based adsorbent.

[0034] Among them, the oxygen-containing functional groups on the surface of the aluminum-based adsorbent and the hydroxyl groups produced by the hydrolysis of the silicon source tetraethyl orthosilicate can be combined through chemical bonds to achieve the synthesis of a silica layer on the surface of the aluminum-based adsorbent, thereby improving the stability of the aluminum-based adsorbent, making it less likely to decompose, and still having a high lithium ion adsorption performance after desorption, and having excellent recycling benefits.

[0035] Furthermore, citric acid contains a large number of hydroxyl and carboxyl structures, which can be chemically bonded to the aluminum-based adsorbent coated with a silica layer, thereby increasing the contact area between the aluminum-based adsorbent and the metal ion solution and increasing the adsorption rate of lithium ions.

[0036] Furthermore, the dosage ratio of the aluminum-based adsorbent, the silicon source, and the citric acid is (0.1-0.2) g:(3-5) mL:(3-4) g.

[0037] Furthermore, the aluminum-based adsorbent is specifically prepared by the following steps: adding aluminum chloride hexahydrate and lithium hydroxide monohydrate to deionized water, stirring evenly, adding a 2 mol / L sodium hydroxide aqueous solution to adjust the pH to 6.5, stirring and reacting for 2 hours, and then centrifuging to obtain a solid, washing the solid with deionized water 5 times, and drying in an oven at 60°C for 10 minutes to obtain an aluminum-based adsorbent.

[0038] Among them, the aluminum ions in aluminum chloride hexahydrate can combine with the hydroxide ions in lithium hydroxide monohydrate to form aluminum hydroxide precipitates. The hydroxide ions produced by the ionization of sodium hydroxide aqueous solution react with the remaining aluminum ions to further promote the precipitation of aluminum hydroxide to form an aluminum-based adsorbent with a two-dimensional layered structure. The interlayers contain a large number of hydrogen ions, and the binding energy for lithium ions is greater than that of metal ions such as cobalt, nickel, and manganese. It shows high selectivity for lithium ions. The interlayers contain a large number of lithium ion adsorption sites, which show high selectivity for lithium ions, thereby being able to separate lithium ions from waste lithium batteries in advance.

[0039] Furthermore, the usage ratio of lithium hydroxide monohydrate, deionized water, and sodium hydroxide aqueous solution is (3-3.2) g: (0.2-0.3) g: (25-35) mL: (5-5.4) mL.

[0040] Furthermore, the composite microbial extractant is prepared by adsorbing composite bacteria on porous carbon and then mixing with 2-naphthalenesulfonic acid.

[0041] Furthermore, the composite bacteria consisted of thermophilic sulfur oxidizing sulfur bacillus and Rhodopseudomonas at (1.3×10 9 -1.7×10 9 ) CFU / mL:(1.3×10 9 -1.9×10 9 )CFU / mL dosage ratio.

[0042] Furthermore, the composite microbial extractant is prepared by the following steps:

[0043] The porous carbon was mixed with the composite bacteria, placed in a constant temperature oscillation for 20 minutes, placed in a closed container, treated under a negative pressure of -0.5 MPa for 10 minutes, taken out, dried at room temperature, placed in deionized water, 2-naphthalenesulfonic acid was added, stirred evenly, allowed to stand for 10 minutes, filtered, washed with deionized water 3 times, and dried in an oven at 30°C for 10 minutes to obtain a composite microbial extractant.

[0044] Among them, porous carbon has a large specific surface area and pore structure, which can adsorb the composite bacteria into the interior of the porous carbon, improve the activity of the composite bacteria, and avoid the composite bacteria being easily affected by temperature, humidity and environment, resulting in low adsorption efficiency. The hydroxyl structure contained on the surface of the porous carbon can be combined with the sulfonic acid group in 2-naphthalenesulfonic acid through chemical bonds, so that 2-naphthalenesulfonic acid is grafted on the surface of the porous carbon, and the sulfonic acid group of 2-naphthalenesulfonic acid can combine with metal elements in waste lithium batteries, thereby improving the recovery efficiency of the composite microbial extractant for valuable metal ions.

[0045] Furthermore, the mass ratio of porous carbon, composite bacteria, and 2-naphthalenesulfonic acid is (2-4) g: (25-35) mL: (0.4-0.6) g.

[0046] Furthermore, the modified porous cobalt oxyhydroxide nanosheets are prepared by reacting the porous cobalt oxyhydroxide nanosheets with a mercapto monomer.

[0047] Furthermore, the porous carbon is prepared by the following steps:

[0048] The Ula grass was washed with deionized water to remove surface soil, dried in an oven at 70°C for 12 h, placed in a tubular furnace, added with a 0.5 mol / L potassium hydroxide aqueous solution, and nitrogen was introduced at a flow rate of 100 mL / min. After 20 min, the temperature was raised to 850°C, carbonized for 2 h, cooled to room temperature, and taken out to obtain porous carbon.

[0049] Among them, potassium hydroxide is used as an activator. At a carbonization temperature of 850°C, the Ula grass is carbonized to form a carbon layer. The potassium hydroxide is decomposed by heat and released in the form of water vapor, forming a porous structure on the surface of the carbon layer with a large specific surface area and pore structure and high adsorption capacity.

[0050] Furthermore, the mass ratio of Ula grass and potassium hydroxide aqueous solution is (2-3) g: (1-3) mL.

[0051] Furthermore, compared with the prior art, the present invention has the following beneficial effects:

[0052] (1) In the technical scheme of the present invention, the aluminum-based adsorbent has a two-dimensional layered structure, contains a large number of hydrogen ions between the layers, has a binding energy for lithium ions greater than that for metal ions such as cobalt, nickel, and manganese, and exhibits a high selectivity for lithium ions, thereby being able to separate lithium ions from waste lithium batteries in advance; a silicon dioxide layer is synthesized on the surface of the aluminum-based adsorbent, thereby improving the stability of the aluminum-based adsorbent, making it difficult to decompose, and still having a high lithium ion adsorption performance after desorption, thereby having excellent recycling benefits; citric acid is grafted onto the surface of the aluminum-based adsorbent coated with the silicon dioxide layer, thereby increasing the contact area between the aluminum-based adsorbent and the metal ion solution, thereby increasing the adsorption rate of lithium ions.

[0053] (2) In the technical scheme of the present invention, the iminodiacetic acid is grafted on the chloromethylated polystyrene molecular chain, which serves as a metal ion chelating resin matrix and has a high binding site, thereby improving the extraction activity of lithium ions. The chloromethylated polystyrene grafted with the iminodiacetic acid reacts with the modified aluminum-based adsorbent to form a cross-linked network structure, and the modified aluminum-based adsorbent is embedded in the cross-linked network structure to form a macroporous adsorption resin, which gives the macroporous adsorption resin a directional adsorption function for lithium ions, thereby being able to first separate lithium ions from waste lithium batteries, reducing the influence of lithium elements on subsequent nickel, cobalt and manganese extraction, and reducing the impurity content in the ternary positive electrode material. In addition, the carboxyl groups in the iminodiacetic acid are consumed, the exchangeability of the macroporous adsorption resin for metal ions is retained, and the macroporous adsorption resin is provided with directional adsorption performance and adsorption sites for lithium ions, thereby further enhancing the extraction efficiency of lithium ions.

[0054] (3) In the technical solution of the present invention, the composite bacteria include thermophilic sulfur oxidizing sulfur bacteria and Rhodopseudomonas. The elemental sulfur and ferrous ions in the composite bacteria provide energy, which can produce sulfuric acid and iron ions to help dissolve the remaining cobalt ions, manganese ions and nickel ions in the positive electrode powder water extract, thereby realizing the recovery of metals from waste lithium-ion battery positive electrode materials.

[0055] (4) In the technical solution of the present invention, the porous carbon has a large specific surface area and pore structure, and the composite bacteria are adsorbed into the interior of the porous carbon to improve the activity of the composite bacteria, avoid the composite bacteria being easily affected by temperature, humidity and environment, and cause low adsorption efficiency. In addition, the composite bacteria are adsorbed into the interior of the porous carbon, and the remaining cobalt ions, manganese ions, and nickel ions in the positive electrode powder water extract can be adsorbed into the interior of the porous carbon, avoiding the influence of other impurities and improving the extraction rate of nickel, cobalt and manganese. 2-naphthalenesulfonic acid is grafted onto the surface of the porous carbon, and the sulfonic acid group of 2-naphthalenesulfonic acid can combine with metal elements in waste lithium batteries, thereby improving the recovery efficiency of the composite microbial extractant for valuable metal ions.

[0056] (5) In the technical solution of the present invention, the recovered metallic lithium forms lithium carbonate, and the recovered metallic nickel, cobalt and manganese form nickel, cobalt and manganese salts, which are used as raw materials for ternary positive electrode materials, and after sintering and iron screening, can be used in ternary positive electrode materials. DETAILED DESCRIPTION

[0057] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0058] The raw materials used in the embodiments of the present invention are as follows: aluminum chloride hexahydrate, lithium hydroxide monohydrate, tetraethyl orthosilicate (analytical grade, purchased from Aladdin Industrial Co., Ltd. (China)); citric acid (purity 99%, purchased from Chengdu Huaxia Chemical Reagent Co., Ltd.); chloromethylated polystyrene (crosslinking degree 6%, Hangzhou Zhengguang Resin Co., Ltd.); N, N-dimethylformamide (analytical grade, purchased from Tianjin Damao Chemical Reagent Factory); iminodiacetic acid (purity 98%, purchased from Shanghai Jingchun Reagent Co., Ltd.); Ula grass (specification: whole grass); 2-naphthalenesulfonic acid (purity 99%, model 120-18-3); malic acid (purchased from Nanjing Songguan Biotechnology Co., Ltd., purity 99%); ascorbic acid (purchased from Qingdao Kester Biotechnology Co., Ltd., purity 98%); thermophilic sulfur oxidizing sulfur bacillus (purchased from Beijing Beina Chuanglian Biotechnology Research Institute); Rhodopseudomonas (model FS-J5014, purchased from Shanghai Fusheng Industrial Co., Ltd.).

[0059] Example 1

[0060] The composite ion exchange resin is specifically prepared by the following steps:

[0061] A1. Add 3.13 g aluminum chloride hexahydrate and 0.27 g lithium hydroxide monohydrate to 30 mL deionized water, stir evenly, add 5.2 mL 2 mol / L sodium hydroxide aqueous solution to adjust the pH to 6.5, stir and react for 2 h, centrifuge to obtain a solid, wash the solid with deionized water 5 times, and dry in an oven at 60°C for 10 min to obtain an aluminum-based adsorbent.

[0062] A2. Add 0.15g of aluminum-based adsorbent to a mixture of 40mL of ethanol and 10mL of deionized water, stir evenly, add 7mL of 20% ammonia water, stir evenly, add 4mL of tetraethyl orthosilicate, stir and react for 2h, filter, wash 3 times with ethanol, wash 3 times with deionized water, dry in an oven at 45℃ for 30min, place in 30mL of deionized water, stir, add 3.5g of citric acid, stir and react at 70℃ for 30min, filter, wash 3 times with deionized water, and dry in an oven at 70℃ for 30min to obtain a modified aluminum-based adsorbent.

[0063] A3. Add 6 g of chloromethylated polystyrene to 100 mL of N,N-dimethylformamide, stir evenly, add 2.5 g of iminodiacetic acid and 0.2 g of sodium hydroxide, stir and react at 80°C for 1 h, add 2.5 g of modified aluminum-based adsorbent, stir and react at 80°C for 30 min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10 min to obtain a composite ion exchange resin.

[0064] Comparative Example 1

[0065] The difference between this comparative example and Example 1 is that the modified aluminum-based adsorbent is replaced by an aluminum-based adsorbent, and the remaining steps and raw materials are the same as Example 1.

[0066] A1. Add 3.13 g aluminum chloride hexahydrate and 0.27 g lithium hydroxide monohydrate to 30 mL deionized water, stir evenly, add 5.2 mL 2 mol / L sodium hydroxide aqueous solution to adjust the pH to 6.5, stir and react for 2 h, centrifuge to obtain a solid, wash the solid with deionized water 5 times, and dry in an oven at 60°C for 10 min to obtain an aluminum-based adsorbent.

[0067] A2. Add 6 g of chloromethylated polystyrene to 100 mL of N,N-dimethylformamide, stir evenly, add 2.5 g of iminodiacetic acid and 0.2 g of sodium hydroxide, stir and react at 80°C for 1 h, add 2.5 g of modified aluminum-based adsorbent, stir and react at 80°C for 30 min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10 min to obtain a composite ion exchange resin.

[0068] Comparative Example 2

[0069] The difference between this comparative example and Example 1 is that no modified aluminum-based adsorbent is added, and the remaining steps and raw materials are the same as Example 1.

[0070] 6 g of chloromethylated polystyrene was added to 100 mL of N,N-dimethylformamide, stirred evenly, 2.5 g of iminodiacetic acid and 0.2 g of sodium hydroxide were added, stirred and reacted at 80°C for 1 h, filtered, washed with deionized water 3 times, and dried in an oven at 70°C for 10 min to obtain an ion exchange resin.

[0071] Example 2

[0072] The composite microbial extractant is specifically prepared by the following steps:

[0073] B1. Wash 2.5 g of Ula grass with deionized water to remove surface dirt, dry it in an oven at 70°C for 12 h, place it in a tubular furnace, add 2 mL of 0.5 mol / L potassium hydroxide aqueous solution, pass nitrogen at a flow rate of 100 mL / min, and after 20 min, heat it to 850°C. After carbonization for 2 h, cool it to room temperature and take it out to obtain porous carbon.

[0074] B2. 1.5×10 9 CFU / mL Thermosulfuric acid bacteria, 1.3×10 9CFU / mL of Rhodopseudomonas was mixed to obtain a composite strain, 3g of porous carbon was mixed with 30mL of the composite strain, placed in a constant temperature oscillation for 20min, placed in a closed container, treated under a negative pressure of -0.5MPa for 10min, taken out, dried at room temperature, placed in 50mL of deionized water, 0.5g of 2-naphthalenesulfonic acid was added, stirred evenly, allowed to stand for 10min, filtered, washed with deionized water 3 times, and dried in an oven at 30°C for 10min to obtain a composite microbial extractant.

[0075] Comparative Example 3

[0076] The difference between this comparative example and Example 2 is that porous carbon and 2-naphthalenesulfonic acid are not added, and the remaining steps are synchronized with Example 2.

[0077] 1.5×10 9 CFU / mL Thermosulfuric acid bacteria, 1.3×10 9 CFU / mL of Rhodopseudomonas were mixed to obtain a composite strain.

[0078] Comparative Example 4

[0079] The difference between this comparative example and Example 2 is that 2-naphthalenesulfonic acid is not added, and the remaining steps are synchronized with Example 2.

[0080] B1. Wash 2.5 g of Ula grass with deionized water to remove surface dirt, dry it in an oven at 70°C for 12 h, place it in a tubular furnace, add 2 mL of 0.5 mol / L potassium hydroxide aqueous solution, pass nitrogen at a flow rate of 100 mL / min, and after 20 min, heat it to 850°C. After carbonization for 2 h, cool it to room temperature and take it out to obtain porous carbon.

[0081] B2. 1.5×10 9 CFU / mL Thermosulfuric acid bacteria, 1.3×10 9 CFU / mL of Rhodopseudomonas was mixed to obtain a composite strain, 3g of porous carbon was mixed with 30mL of the composite strain, placed in a constant temperature oscillation for 20min, placed in a sealed container, treated under a negative pressure of -0.5MPa for 10min, taken out, and dried at room temperature to obtain a composite microbial extractant.

[0082] Example 3

[0083] A process for extracting lithium first and then nickel, cobalt and manganese comprises the following steps:

[0084] S1. 30g of waste lithium batteries were placed in 80mL of 2.7mol / L sodium chloride solution for discharge, disassembled, placed in a grinder for coarse crushing, pyrolyzed, and sieved to obtain pre-treated positive electrode powder. The pyrolysis temperature was 450℃ and the sieve mesh size was 300 mesh.

[0085] S2. Mix 10g of malic acid and 50mL of deionized water to obtain an organic acid solution, mix 15g of pretreated positive electrode powder and 60mL of organic acid solution, stir, add 3g of composite ion exchange resin, stir for 1h, filter to obtain solid A and water extract, and post-treat solid A to obtain lithium carbonate. Among them, the post-treatment of solid A is specifically as follows: add 3.8g of solid A to 60mL of deionized water, oscillate at 60rpm for 1h, collect the filtrate by filtration, add 10mL of 0.2g / mL sodium carbonate aqueous solution to the filtrate, stir at 80°C for 3h, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 10min.

[0086] S3. 50 mL of the water extract was mixed with 5 g of the composite microbial extractant, stirred for 1.5 h, filtered to obtain solid B, and solid B was desorbed to obtain nickel-cobalt-manganese salt. The desorption treatment of solid B was specifically as follows: 4.3 g of solid B was added to 30 mL of 2 mol / L nitric acid aqueous solution, soaked for 20 min until the metal ions were desorbed, filtered, and the filtrate was collected. The filtrate was stirred at 90 ° C for 2 h and cooled to room temperature.

[0087] Example 4

[0088] A process for extracting lithium first and then nickel, cobalt and manganese comprises the following steps:

[0089] S1. 35g of waste lithium batteries were placed in 90mL of 2.7mol / L sodium chloride solution for discharge, disassembled, placed in a grinder for coarse crushing, pyrolyzed, and sieved to obtain pre-treated positive electrode powder. The pyrolysis temperature was 450℃ and the sieve mesh size was 300 mesh.

[0090] S2. Mix 11g of ascorbic acid and 55mL of deionized water to obtain an organic acid solution, mix 18g of pretreated positive electrode powder and 70mL of organic acid solution, stir, add 5g of composite ion exchange resin, stir for 1h, filter to obtain solid A and water extract, and post-treat solid A to obtain lithium carbonate. Among them, the post-treatment of solid A is specifically as follows: add 3.8g of solid A to 60mL of deionized water, oscillate at 60rpm for 1h, collect the filtrate by filtration, add 10mL of 0.2g / mL sodium carbonate aqueous solution to the filtrate, stir at 80°C for 3h, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 10min.

[0091] S3. 60 mL of the water extract was mixed with 6 g of the composite microbial extractant, stirred for 1.5 h, filtered to obtain solid B, and solid B was desorbed to obtain nickel-cobalt-manganese salt. The desorption treatment of solid B was specifically as follows: 4.3 g of solid B was added to 30 mL of 2 mol / L nitric acid aqueous solution, soaked for 20 min until the metal ions were desorbed, filtered, and the filtrate was collected. The filtrate was stirred at 90 ° C for 2 h and cooled to room temperature.

[0092] Example 5

[0093] A process for extracting lithium first and then nickel, cobalt and manganese comprises the following steps:

[0094] S1. Place 40g of waste lithium batteries in 100mL of 2.7mol / L sodium chloride solution for discharge, disassemble, place in a grinder for coarse crushing, pyrolyze, and sieve to obtain pre-treated positive electrode powder. The pyrolysis temperature is 450℃; the sieve mesh size is 300 mesh.

[0095] S2. Mix 12g of oxalic acid and 60mL of deionized water to obtain an organic acid solution, mix 20g of pretreated positive electrode powder and 80mL of organic acid solution, stir, add 7g of composite ion exchange resin, stir for 1h, filter to obtain solid A and water extract, and post-treat solid A to obtain lithium carbonate. Among them, the post-treatment of solid A is specifically as follows: add 3.8g of solid A to 60mL of deionized water, oscillate at 60rpm for 1h, collect the filtrate by filtration, add 10mL of sodium carbonate aqueous solution with a concentration of 0.2g / mL to the filtrate, stir at 80°C for 3h, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 10min.

[0096] S3. 70 mL of the water extract was mixed with 7 g of the composite microbial extractant, stirred for 1.5 h, filtered to obtain solid B, and solid B was desorbed to obtain nickel-cobalt-manganese salt. The desorption treatment of solid B was specifically as follows: 4.3 g of solid B was added to 30 mL of 2 mol / L nitric acid aqueous solution, soaked for 20 min until the metal ions were desorbed, filtered, and the filtrate was collected. The filtrate was stirred at 90 ° C for 2 h and cooled to room temperature.

[0097] Comparative Example 5

[0098] The difference between this comparative example and Example 4 is that the composite ion exchange resin is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 4.

[0099] Comparative Example 6

[0100] The difference between this comparative example and Example 4 is that the composite ion exchange resin is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 4.

[0101] Comparative Example 7

[0102] The difference between this comparative example and Example 4 is that the composite microbial extractant is replaced by the substance prepared in Comparative Example 3, and the remaining steps are synchronized with Example 4.

[0103] Comparative Example 8

[0104] The difference between this comparative example and Example 4 is that the composite microbial extractant is replaced by the substance prepared in Comparative Example 4, and the remaining steps are synchronized with Example 4.

[0105] Application of a process for extracting lithium first and then nickel, cobalt and manganese in ternary positive electrode materials:

[0106] The lithium carbonate and nickel-cobalt-manganese salt prepared above are mixed, sintered at 800° C., and iron is screened to obtain a ternary positive electrode material.

[0107] A process method of first extracting lithium and then extracting nickel, cobalt and manganese in Examples 3-5 and Comparative Examples 5-8 is now tested; the Li content in 20g of the pretreated positive electrode powder of the present invention is 11.67%, the Ni content is 28.87%, the Co content is 9.82%, and the Mn content is 9.62wt%).

[0108] 3.8 g of solid A in Example 4 was added to 60 mL of deionized water and shaken at 60 rpm for 1 h to desorb the saturated composite ion exchange resin. Samples were taken every 250 mL until the pH value of the adsorption column effluent was about 1. The desorption was stopped, the content and purity of lithium ions in the desorbed liquid were determined, and the recovery rate was calculated.

[0109] 4.3 g of solid B in Example 4 was added to 30 mL of 2 mol / L nitric acid aqueous solution, and the mixture was immersed for 20 min until the metal ions were desorbed. The mixture was filtered and the filtrate was collected. The content and purity of nickel, cobalt and manganese in the filtrate were determined by atomic absorption spectrophotometer, and the recovery rate was calculated.

[0110] The lithium carbonate and nickel-cobalt-manganese salt prepared above were mixed, sintered at 800°C, and iron was screened to obtain a ternary positive electrode material. The charge and discharge were tested at a current density of 200 mA / g, and the first discharge capacity and the first discharge efficiency were recorded. The purity of the ternary positive electrode material prepared by the recycled metal was tested based on the discharge capacity and the first discharge efficiency. The test results of the preparation are shown in Table 1 below:

[0111] Table 1: Test results

[0112] project Li recovery rate / % Ni recovery rate / % Co recovery rate / % Mn recovery rate / % Discharge capacity (mAh / g) Discharge efficiency / % Example 3 98.6 98.2 99.1 99.5 189.6 92.3 Example 4 99.3 98.9 99.5 99.6 190.2 92.8 Example 5 98.5 98.7 99.3 99.4 188.9 92.5 Comparative Example 5 90.1 92.2 93.2 93.5 158.9 82.2 Comparative Example 6 80.6 90.2 91.2 91.5 142.1 75.5 Comparative Example 7 98.6 80.3 82.3 82.5 140.1 73.6 Comparative Example 8 98.3 93.6 94.5 95.1 170.6 86.9

[0113] It can be seen from the data in Table 1 that in Comparative Example 5, the composite ion exchange resin prepared by replacing the modified aluminum-based adsorbent with an aluminum-based adsorbent is used for the extraction of lithium ions, and its lithium recovery rate is lower than that of Examples 3-5. This may be because a silicon dioxide layer is synthesized on the surface of the aluminum-based adsorbent, which improves the stability of the aluminum-based adsorbent, and citric acid is grafted on the surface of the aluminum-based adsorbent coated with the silicon dioxide layer, which increases the contact area between the aluminum-based adsorbent and the metal ion solution, thereby increasing the adsorption rate of lithium ions; Comparative Example 6 is a composite ion exchange resin prepared without adding a modified aluminum-based adsorbent for the extraction of lithium ions, and its lithium recovery rate is lower than that of Examples 3-5. This may be because the aluminum-based adsorbent has a two-dimensional layered structure, contains a large amount of hydrogen ions between the layers, and exhibits a high selectivity for lithium ions, thereby The purpose of first separating lithium ions from waste lithium batteries is to achieve the purpose of first separating lithium ions from waste lithium batteries; in comparative example 7, the composite microbial extractant prepared without adding porous carbon and 2-naphthalenesulfonic acid is used for the extraction of nickel, cobalt and manganese, and its nickel, cobalt and manganese extraction rate is lower than that of examples 3-5. This may be because the porous carbon has a large specific surface area and pore structure, and the composite bacteria are adsorbed into the interior of the porous carbon, thereby improving the activity of the composite bacteria and avoiding the composite bacteria from being easily affected by temperature, humidity and environment, resulting in low adsorption efficiency; in comparative example 8, the composite microbial extractant prepared without adding 2-naphthalenesulfonic acid is used for the extraction of nickel, cobalt and manganese, and its nickel, cobalt and manganese extraction rate is lower than that of examples 3-5. This may be because the sulfonic acid group of 2-naphthalenesulfonic acid can combine with metal elements in waste lithium batteries, thereby improving the recovery efficiency of the composite microbial extractant for valuable metal ions.

[0114] The data in Table 1 illustrate that Example 3-5 is a process method for extracting lithium first and then nickel, cobalt and manganese. First, lithium salt is recovered, and then nickel, cobalt and manganese are extracted to form nickel, cobalt and manganese, and the ternary positive electrode material is prepared as a raw material. In this method, lithium is extracted first, which reduces the influence of lithium element on the subsequent extraction of nickel, cobalt and manganese, and reduces the impurity content in the ternary positive electrode material. The waste lithium battery is placed in a sodium chloride solution for discharge, disassembled, placed in a grinder for coarse crushing, pyrolyzed and sieved to obtain a pre-treated positive electrode powder; the pre-treated positive electrode powder and the organic acid solution are mixed, stirred, and a composite ion exchange resin is added, filtered to obtain solid A and water extract, and solid A is post-treated to obtain lithium carbonate; the water extract is mixed with a composite microbial extractant, filtered to obtain solid B, and solid B is desorbed to obtain nickel, cobalt and manganese salts to meet the test performance requirements, while the process method of extracting lithium first and then nickel, cobalt and manganese in Comparative Examples 5-8 does not meet the performance requirements, indicating that the present invention extracts lithium first and then nickel, manganese and cobalt, reducing the influence of lithium element on the subsequent extraction of nickel, cobalt and manganese.

[0115] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0116] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A process for extracting lithium first and then nickel, cobalt and manganese, characterized in that: The following steps are involved: S1. The waste lithium battery is placed in a sodium chloride solution for discharge, disassembled, placed in a grinder for coarse crushing, pyrolyzed, sieved, and a pretreated positive electrode powder is obtained; S2. The pretreated cathode powder and the organic acid solution are mixed, stirred, a composite ion exchange resin is added, filtered, and a solid A and an aqueous solution are obtained. The solid A is post-treated to obtain lithium carbonate; The composite ion exchange resin is prepared by reacting iminodiacetic acid with chloromethylated polystyrene, adding a modified aluminum-based adsorbent, and stirring the reaction; The modified aluminum-based adsorbent is prepared by mixing an aluminum-based adsorbent with a silicon source and then adding citric acid; The preparation method of the aluminum-based adsorbent is as follows: aluminum chloride hexahydrate and lithium hydroxide monohydrate are added to deionized water, stirred, a 2 mol / L sodium hydroxide aqueous solution is added to adjust the pH to 6.5, centrifuged, washed, and dried to obtain the aluminum-based adsorbent; S3. The aqueous extract is mixed with a composite microbial extractant, filtered, and solid B is obtained. The solid B is desorbed to obtain nickel-cobalt-manganese salt; The preparation method of the composite microbial extractant is as follows: the porous carbon is mixed with the composite bacteria, placed under constant temperature oscillation for 20 minutes, placed in a closed container, treated under a negative pressure of -0.5 MPa for 10 minutes, taken out, dried at room temperature, placed in deionized water, 2-naphthalenesulfonic acid is added, stirred evenly, allowed to stand for 10 minutes, filtered, washed with deionized water 3 times, and dried in an oven at 30°C for 10 minutes to obtain the composite microbial extractant; The composite bacteria are composed of thermophilic sulfur oxidizing sulfur bacillus and rhodopseudomonas according to (1.3×10 9 -1.7×10 9 )CFU / mL:(1.3×10 9 -1.9×10 9 )CFU / mL dosage ratio.

2. The process of extracting lithium first and then nickel, cobalt and manganese according to claim 1, characterized in that: The silicon source is selected from any one of tetraethyl orthosilicate, dimethyldiethoxysilane and diphenyldiethoxysilane.

3. The process of extracting lithium first and then nickel, cobalt and manganese according to claim 1, characterized in that: The organic acid solution is prepared by mixing an organic acid and deionized water in a dosage ratio of (10-12) g:(50-60) mL; the organic acid is selected from any one of malic acid, acetic acid, oxalic acid, citric acid and ascorbic acid.

4. The process of extracting lithium first and then nickel, cobalt and manganese according to claim 1, characterized in that: The post-treatment of the solid A specifically includes the following steps: adding the solid A to deionized water, shaking at a rate of 60 rpm for 1 hour, collecting the filtrate by filtration, adding a 0.2 g / mL sodium carbonate aqueous solution to the filtrate, stirring, filtering, washing, and drying to obtain lithium carbonate.

5. The process of extracting lithium first and then nickel, cobalt and manganese according to claim 1, characterized in that: The desorption treatment of the solid B specifically includes the following steps: adding the solid B into a 2 mol / L nitric acid aqueous solution, soaking for 20 minutes until the metal ions are desorbed, filtering, collecting the filtrate, stirring the filtrate at 90° C. for 2 hours, and cooling to 30° C. to obtain nickel-cobalt-manganese salt.

6. The process of extracting lithium first and then nickel, cobalt and manganese according to claim 1, characterized in that: The concentration of the sodium chloride solution is 1-3 mol / L; the pyrolysis temperature is 200-600° C.; and the aperture of the sieve is 200-400 meshes.

7. An application of the process of first extracting lithium and then extracting nickel, cobalt and manganese as claimed in any one of claims 1 to 6 on ternary positive electrode materials, characterized in that: The lithium carbonate and nickel-cobalt-manganese salt are mixed, sintered, and iron screened to obtain a ternary positive electrode material.

Citation Information

Patent Citations

  • Lithium resource and salt-alkali recycle method

    CN107768760A

  • Method and system for recovering lithium and manganese from waste lithium manganate battery

    CN109207725A